Transcriptomics Analysis Indicates Trifarotene Reverses Acne-Related Gene Expression Changes - Dreno, Brigitte; Chavda, Rajeev; Julia, Valerie; Khammari, Amir; Blanchet-Réthoré, Sandrine; Krishnaswamy, Jayendra Kumar (Frontiers in Medicine, 2021)
Background and Objectives: Trifarotene is a topical retinoid selective for retinoic acid receptor gamma that was recently approved for treatment of acne vulgaris. We performed a gene expression analysis to identify the molecular and cellular impact of trifarotene treatment on acne papules. Methods: In this open-label prospective study, subjects with moderate inflammatory acne of the back were treated with trifarotene 0.005% or vehicle cream on dedicated areas for 27 days, and 4 biopsies were collected from each subject (1 from skin without a visible acne lesion and three at the site of an acne papule: one baseline, one after vehicle treatment, and one after trifarotene treatment). Large scale gene expression profiling of the biopsies was performed using Affymetrix technology, and treatment-specific gene expression profiles were generated using statistical modeling. Ingenuity Pathway Analysis was used to analyze biologic pathways. Using single-cell RNAseq data, in silico deconvolution of transcriptomics data was performed to identify cellular signatures. Results: We discovered a unique set of 67 genes downregulated by trifarotene that are primarily involved in cellular migration, inflammation, and extracellular matrix reorganization. Changes in cellular expression were similar in both trifarotene-treated and spontaneously-resolving lesions. However, only trifarotene treatment impacted SPP1+ macrophages, a subset of highly proliferative macrophages recently identified in fibrotic tissue. Conclusions: These results show that trifarotene has a novel action in acne treatment by affecting epidermal and immune components of acne pathogenesis.